On the Relationship of Interoceptive Accuracy and Attention: A Controlled Study With Depressed Inpatients and a Healthy Cohort - Schultchen, Dana; Schneider, Carolin; Berberich, Götz; Zaudig, Michael; Erle, Thorsten M.; Pollatos, Olga (Frontiers in Psychology, 2021)
Objective Previous research has shown reduced interoceptive accuracy (IAcc) in depression. Attention deficit represents a key symptom of depression. Moreover, IAcc is positively correlated with attention. There is no study that investigates the effect of depression on IAcc and attention. The aim of this study is to examine the mediating effect of IAcc on depression and attention. Methods Thirty-six depressed patients from the Psychosomatic Clinic in Windach were matched with 36 healthy controls according to age and sex and were assessed at Ulm University. All participants completed the Beck Depression Inventory-II, the heartbeat perception task to examine IAcc, and the d2 test assessing selective attention. Results Depressed patients showed attention deficits—both for general visual attention and IAcc—compared to healthy controls. The mediation analyses revealed that the relationship between depression and attention is not mediated via IAcc. Furthermore, depression predicts IAcc and attention, but these effects are direct and largely unaffected by the respective other variable. Discussion The results of the present study highlight both interoceptive as well as attention deficits in depressed patients. No clear mediation between these variables could be shown in this study. More elaborative research is needed to clarify whether different approaches to improve IAcc are effective for these deficits in depressed patients and could therefore be of importance as an additional aspect of therapy in depression.